Study on the Isothermal Quenching Process of C55E Steel Chain Plates with JMatPro Software - Dai Yujie; Wang Kui (Jixie chuandong)
The phase transformation temperature of C55E material can be obtained by simulating TTA curve, CCT curve and TTT curve with material simulation software JMatPro. The isothermal quenching process of C55E steel chain plates is formulated by the obtained transformation temperature. The results show that the isothermal quenching process parameters formulated by the material simulation software JMatPro are the quenching temperature of 850 ℃, the isothermal temperature of 310 ℃, and the isothermal time of 25 min. The hardness of the chain plate after isothermal quenching meets the technical requirements, and the strength, fatigue and other properties of the chain are close to the 50CrV material treated by the same process.